Justification of Administrative Decisions on the Basis of Management Accounting Data - M. B. Zhernakova; I. M. Shestakova (Управление)
The article analyzes the place and role of management accounting in making managerial decisions. The authors believe that the current economic crisis demands flexibility, control and efficiency strategic and operational decisions. The article describes the stages of development of management accounting, a comparison of the content of such economic categories as management accounting, controlling, planning, economic activity, and economic calculation. Given the periods of economic crises and changes in management accounting. The article highlights the processes of improving the management in the USSR. The authors consider the characteristics of strategic and operational management accounting, purpose of management accounting in the organization, the requirements to the information formed in system of management accounting.